2019
DOI: 10.1080/26415275.2019.1684201
|View full text |Cite
|
Sign up to set email alerts
|

The effects of artificial aging on high translucent zirconia

Abstract: Zirconia is known for its high strength but lacking translucency. Recently, a new type of high translucent zirconia, 5 mol% yttria partially stabilized zirconia (5Y-PSZ), with a larger fraction of cubic zirconia phase has become commercially available. However, the resistance to aging of these commercially available zirconia materials is not yet fully established. Purpose: The aim of the present study was to analyze the effects of artificial aging on surface roughness, transparency, phase transformation and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
3
7
0
1
Order By: Relevance
“…A2 pre-shaded compared A2 liquid shaded before and after age, as well as A2 pre-shaded versus A2 liquid shaded after aging, all showed a decrease in translucency; however, this decline was statistically non-significant. This result was in agreement with Kou et al (2019) (55) who investigated the impact of artificial aging on highly translucent zirconia and came to the conclusion that the translucency of zirconia ceramic was unaffected by aging.…”
Section: Discussionsupporting
confidence: 91%
“…A2 pre-shaded compared A2 liquid shaded before and after age, as well as A2 pre-shaded versus A2 liquid shaded after aging, all showed a decrease in translucency; however, this decline was statistically non-significant. This result was in agreement with Kou et al (2019) (55) who investigated the impact of artificial aging on highly translucent zirconia and came to the conclusion that the translucency of zirconia ceramic was unaffected by aging.…”
Section: Discussionsupporting
confidence: 91%
“…The included articles were all in English and were published between 2014 and 2020. Of the 13 studies included in the systematic review, 1 study performed color measurements [ 37 ], 8 studies performed translucency evaluations [ 13 , 39 41 , 49 52 ], and 4 studies performed both types of investigations [ 22 , 25 , 53 , 54 ]. All included studies were laboratory studies measuring the color and/or translucency with a spectrophotometer.…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessing the effect of autoclave aging on monolithic 5Y‐Z and 3Y‐Z have shown that 5Y‐Z has the lowest biaxial flexural strength values, but no low temperature degradation was found after autoclave aging (34,47). Another study examining the effect of autoclave aging on two types of 5Y‐Z materials (DD cubeX 2 and Prettau Anterior), revealed a difference in flexural strength between the two zirconia materials (48). DD cubeX 2 had a statistically significantly higher mean flexural strength than Prettau Anterior, both before and after artificial aging for 10 h. However, DD cubeX 2 showed a statistically significant reduction in flexural strength after artificial aging.…”
Section: Discussionmentioning
confidence: 99%